(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
This article delves into diverse and innovative methods employed in the formation of speech activity among preschool children. It explores the role of play-based learning, parental involvement, early intervention, holistic speech activities, and the celebration of progress. The article emphasizes the importance of a collaborative approach involving educators, parents, and speech therapists in nurturing confident communicators during early childhood education.